Hubungan Tingkat Pengetahuan Ibu tentang Pencegahan Demam Tifoid dengan Kejadian pada Anak di Aceh Utara - Annisa Naila Dzakira; Julia Fitriany; Sarah Rahmayani Siregar; Fury Maulina; Mardiati Mardiati (Jurnal Ventilator, 2026)
Typhoid fever is a systemic infectious disease caused by Salmonella typhi and remains a public health concern, particularly among children. In 2019, the prevalence of typhoid fever in North Aceh reached 0.7%. The high incidence of typhoid fever among children suggests that household sanitation practices may not be optimally implemented, which is presumed to be associated with mothers’ knowledge of typhoid fever prevention. This study aimed to assess mothers’ knowledge of preventive measures against typhoid fever and analyze its association with typhoid fever incidence among pediatric patients at Cut Meutia Regional General Hospital, North Aceh. This analytical quantitative study used a cross-sectional design involving 101 mothers of pediatric patients who met the inclusion criteria. Data were collected through a maternal knowledge questionnaire and medical records, then analyzed using univariate and bivariate analyses with the Chi-square test. The results showed that most children were aged 2–6 years (46.5%) and female (59.4%). Most mothers were housewives (73.3%) and had completed senior high school education (53.5%). Typhoid fever was found in 46 children (45.5%), while most mothers had good knowledge of typhoid fever prevention (53.5%). Bivariate analysis showed that children with typhoid fever were more likely to have mothers with poor knowledge, whereas children without typhoid fever were more likely to have mothers with good knowledge. A significant association was found between maternal knowledge and typhoid fever incidence in children (p=0.000). These findings highlight the importance of strengthening maternal health education as part of typhoid fever prevention in children.